Integrated dry NO sub x /SO sub 2 emissions control system - United States. Department of Energy. (Public Service Co. of Colorado, Denver, CO (United States), 1991)
This project's goal is to demonstrate the removal up to 70% of the NOsub x and 70% of the SOsub 2 emissions from coal fired utility boilers. It will establish an alternative emissions control technology integrating a combination of several processes, while minimizing capital expenditures and limiting waste production to dry solids that are handled with conventional ash removal equipment. These processes include low-NOsub x burners, NOsub x ports and urea injection for NOsub x control, sodium or calcium based sorbent injection for SOsub 2 control, and flue gas humidification to enhance the reactivity of the SOsub 2 control compound.